Non-space: The Metaphysics of Space In The Information Age - Zijlstra, Sybrand (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
The computer will become more and more influential as a mediator between man and his environment, due to its evolution as a device and increasing ubiquity. A growing number of people will own a personal computer or computer-like devices, such as cell phones, even though a ‘digital divide’ will continue to exist, separating social groups within societies. To denote a computer-mediated environment, the term non-space is proposed, derived from Vilém Flusser’s non-things which basically refers to computer-programs. Non-space is relative, fluid, non-material and non-locatable. Spatial metaphors, still used in present-day computer-interfaces, are inherently deficient and will be replaced by a more direct and intimate interaction with the computer. Life in non-space is essentially provisional, which causes a new existential anxiety. In the not so distant future, large portion of humanity will end up living their lives in ‘augmented reality’, a hybrid of the real world and non-space.